ANALISIS DAMPAK PENGOLAHAN HASIL PERIKANAN MENGGUNAKAN METODE LIFE CYCLE ASSESSMENT (LCA): STUDI LITERATUR - Nadia Athirafitri; Nastiti Siswi Indrasti; Andes Ismayana (Jurnal Teknologi Industri Pertanian, 2022)
The development of the fishery industry not only provides advantages, but has a significant impact on theenvironment. Life Cycle Assessment (LCA) can be used to identify positive and negative environmental impacts ofa process or product, find opportunities for processing and product development, comparing and analyzing theimpact of the environment caused and calculat the environmental impacts resulting from a quantitative product.Life Cycle Assessment (LCA) according to the ISO 14040 consists of four stages, namely the determination of thegoals and scope, inventory analysis, impact analysis, and interpretation. The purpose of this literature study wasto identify and quantify the potential pollution and environmental impact caused by the production process in thefishery industry. Fishery products studied were fish fillets and canned fish products. The potential environmentalimpacts of processing of fishery industry cover greenhouse gas (GHG), acidification, and eutrophication. Thedescription of the environmental impact analysis in the fishery processing industry was explained in this work. Theliterature data indicates that the impact of GHG is caused by CO2, the impact of acidification is generated by SO2, and the effects of eutrophication are generated by PO43-. Recommendations for improvements are replacing energysources and fuels.Keywords: acidification, eutrophication, fishery processing industry, GHG, life cycle assessment